Increasing Cafe D'Lagoon's Income through Collaboration with Local MSMEs: Meningkatkan Pendapatan Cafe D'Lagoon melalui Kolaborasi dengan UMKM Lokal - Khumairoh Hafiz A’inun Naim; Virginia Mandasari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Cafe D'Lagoon is one of the cafes in the area that has great potential to grow, but the income generated is still not optimal. One solution to overcome this is to collaborate with local MSMEs. This community service program aims to facilitate an increase in Cafe D'Lagoon's income by combining local MSME products into cafe services. This activity is carried out by involving local food industry MSMEs to promote their products in the cafe. In addition, this activity also has the potential to have an impact on increasing cooperation between cafes and local MSMEs, which provides benefits for both parties. The results of the activity show that cafe income has increased and MSME products can be promoted more widely. In the long term, this activity will create a sustainable cooperation model between cafes and local MSMEs.